Individual Differences in the Order/Chaos Balance of the Brain Self-Organization - Cordova-Gonzalez, F; Palominos-Villavicencio, F; Canete-Arratia, L; Diaz-Munoz, H (Springer Science and Business Media Deutschland GmbH, 2015)
We used fractal geometry and fractal dimension introductory argumentation as a framework to start understanding dynamical and complex biological systems to then introduce Hurst exponent estimation of chaos/no-chaos balance trend to explore the phenomenology and the information content of EEG data through time. We searched for measure proxy dynamical variables as potential biomarkers and/or endo-phenotypes that help us to figure out the multidimensionality and different time-scale of simultaneous and crossed functional phenomena that manifests in the brain during executing any challenging task. We found consistencies in the way intra- and inter-individual differences express themselves through the EEG time series data analysis, and some degree of specificity and specialization in the frontal, temporal and occipital locations as well as brain interhemispheric cross-talk interaction modulating the chaos/no-chaos balance in the brain, during a projective process of imaging a dancing choreography. We recorded the brain activity of N = 9 professional dancers while executing the instruction of to imagine (by mean of a typical projective visualization) a future dancing performance as part of the requirement for to approve a specialization modern dance course and workshop (Kosmos In Movement, 2015). © 2015, Springer-Verlag Berlin Heidelberg.